Developed Empirical Models for the Estimation of Global Solar Radiation with Sunshine Hours and other Meteorological Data on a Horizontal Surface in Some Cities in North Central Geopolitical Zone in Nigeria - C.I. , Elekachi; A.O.C. , Nwokoye; N.L. , Okoli (African Journal of Education,Science and Technology (AJEST), 2017)
Measurement of global solar radiation and its components is not possible for all locations due to non-availability of solar radiation measuring instruments. This prompted the use of different empirical models that based on climatological parameters of a location for the estimation of global solar radiation. In this study, monthly measured global solar radiation Hm, monthly mean extraterrestrial global solar radiation Ho, monthly mean daylight hours (N) and monthly mean hours of bright sunshine (n), latitudes (), maximum temperature (Tmax) and relative humidity (RH) as geographical and meteorological parameters for estimating monthly mean global solar radiation in Abuja (9.067 N, 7.483 E), Minna (9.613 N, 6.557 E) and Ilorin (8.500 N, 4.550 E) cities in north central geopolitical zone of Nigeria for the period of 11 years (2000 – 2010) were investigated. Meteorological data for this investigation were gotten from the archives of National Aeronautics and Space Administration (NASA). Using empirical Angstrom model as a base model, sunshine based regression equations, maximum temperature and relative humidity based equations were developed for the cities. The correlation coefficient (R) and Root Mean Square Error (RMSE), Mean Bias Error (MBE), Mean Percentage Error (MPE) and t - stat values were determined for each proposed models and were used to evaluate the performance of each of the developed models.